Influence of Inclusions in the Corrosion Behavior of Plasma Nitrided Stainless Steel. Issue 8 (18th January 2023) - Escalada, Lisandro; Dalibon, Eugenia L.; Brühl, Sonia Patricia; Manova, Darina; Mändl, Stephan; Simison, Silvia
Abstract : Plasma nitriding is a well‐established technique to improve hardness and tribological properties of austenitic stainless steel. It is proved that it is also possible to preserve the corrosion resistance after nitriding by controlling the process parameters such as time and temperature, obtaining the so‐called S phase. Herein, the corrosion behavior is evaluated for nitrided layers produced by three different plasma treatments: DC plasma nitriding, plasma immersion ion implantation (PIII), and low‐energy ion implantation (LEII), using different parameters in order to obtain the S‐phase in thickness from 1.2 to about 6 μm without nitride precipitation. The microstructure and chemical composition of the nitrided layers is characterized by means of X‐ray diffraction, secondary‐ion mass spectroscopy, and scanning electron microscopy–focused ion beam. The corrosion behavior is evaluated by means of the cyclic polarization tests in NaCl solution. The morphology of the corrosion attack is studied by optical microscopy and SEM‐FIB, revealing a change from crevice to pitting after the nitriding process. The inclusions are observed to be corrosion initiation sites. Due to this, the thickest nitrided layers (with high N concentration) show better corrosion behavior than the thinner ones. Abstract : Herein, the corrosion mechanism of austenitic stainless steel AISI 316L which is plasma nitrided by three different techniques is dealt with. The paper is focused on the nitrided layer characteristics, and the relation between the inclusions and the S phase thickness is studied.